2019
DOI: 10.4103/ijpvm.ijpvm_429_17
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in different chronic diseases and its related factors

Abstract: Background: Quality of life (QoL) is an important tool for evaluating the effect of a disease as well as effects of treatment interventions. The present study is aimed to investigate QoL of the patients with various prevalent chronic diseases in Iran. Methods: In a cross-sectional study, 625 patients with one of the prevalent chronic diseases were assessed. Participants were recruited via convenient sampling method in special clinics of chronic diseases in three educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 15 publications
2
25
1
4
Order By: Relevance
“…Numerous studies [13][14][15][16][17] have demonstrated effects of psychological or medical afflictions on, respectively, mental or physical health-related Quality of Life (HRQoL), i.e., perceived impairments in individuals' health status caused by emotional or bodily factors [18,19]. Tinnitus-related distress [20][21][22], anxiety [23], depressive symptoms [24,25], and somatization symptoms [26][27][28] have all been reported to have a negative impact on patients' health-related quality of life (HRQoL).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies [13][14][15][16][17] have demonstrated effects of psychological or medical afflictions on, respectively, mental or physical health-related Quality of Life (HRQoL), i.e., perceived impairments in individuals' health status caused by emotional or bodily factors [18,19]. Tinnitus-related distress [20][21][22], anxiety [23], depressive symptoms [24,25], and somatization symptoms [26][27][28] have all been reported to have a negative impact on patients' health-related quality of life (HRQoL).…”
Section: Introductionmentioning
confidence: 99%
“…QoL assessment is an important tool to evaluate the effects of diseases and therapeutic interventions. QoL is related to an individual’s level of self-perceived satisfaction with life [ 23 ]. The brief version of the World Health Organization Quality of Life Scale: Brief version (WHOQOL-BREF) has good psychological measurement characteristics, serving as an appropriate tool for cross-cultural assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The HRQOL is dependent on the number of the chronic diseases and is higher with the lighter burden of diseases [ 21 ]. For example, hypertension and diabetes are experienced with a minor decrease in HRQOL than depression, cancer, asthma and chronic obstructive pulmonary disease [ 22 , 23 ]. One purpose of the care plan is to support continuity which is particularly important in patients with chronic illnesses and improving the quality of care [ 24 – 29 ].…”
Section: Backroundmentioning
confidence: 99%